Autonomous, Connected Ultrasonic Microsystem Dedicated to Monitoring the Pathophysiology of the Phonic and Respiratory Apparatus: A Recent Study - Sawan, M.; Reda, H.; Saad, N.; Bin, S.; Nassar, G. (Newest Updates in Physical Science Research Vol. 11, 2021)
This work tackles a combination of two technological fields: "integrated ultrasonic biosensors" and "connected modules" coupled with “Artificial Intelligence” algorithms to provide healthcare professionals with additional indices offering multidimensional information and a “Decision Support” tool. This device comprises a connected telemedical platform (PC or Smartphone) dedicated to the objective and remote assessment of pathophysiological states resulting from dysphonia of laryngeal origin or respiratory failure of inflammatory origin. Based on this study, the most appropriate biomechanical factors were determined and quantified to help optimize the sensor/biological tissue interface conditions.